Smart mobile emergency system for paramedic user (SMES) - Khalisah, Abdul Basid (2014)
Today, computerized systems are needed in every organizations and business sector. It can minimize the human's workload and the organization might need just one worker for one each system. Furthermore, technology helps people to reduce their time by using electronic systems instead of recording data manually. For that reason, ambulance emergency systems are built in health sector to make process and treatment that can be made in a more appropriate and faster way.Ambulance Emergency System is a paperless electronic application that is designed with high flexibility and ease of usage, implemented for health sector to handle treatment with patient in more efficient way. There are many kinds of ambulance emergency system that exist nowadays. This system is generally built to receive the patient's details correctly in faster way. SMES is developed as portable medical device that allows in tele-consultation, also in mobile healthcare. This system is used for paramedic user (ambulance site), where expert assistance is needed for patients to give directly treatment on site and send the information to the emergency department and the doctor. The information will be given in picture and video form for the preparation before patient arrival. The emergency department and the doctor will receive the information from the paramedic (ambulance site). With this system, they are ready for the next action and do the preparation before the patient arrival. It can reduce the time taken for patient treatment.